Psychosocial work environment, job mobility and gender differences in turnover behaviour: a prospective study among the Swedish general population - Söderberg, Mia (BioMed Central, 2014)
BACKGROUND: Throughout the literature, substantial evidence supports associations between poor psychosocial work characteristics and a variety of ill-health outcomes. Yet, few reports strategies workers carry out to improve detrimental work conditions and consequently their health, such as changing jobs. The aim of this study was to examine if adverse psychosocial work exposure, as measured with the job demand-control and effort-reward imbalance models, could predict job mobility over a 5 years observation period. METHOD: Participants were working men and women (n = 940; 54.3% women), aged 24–60 years from the population of Gothenburg and surrounding metropolitan area. Job demand-control and effort-reward variables were compared with independent t-tests and chi2-test in persons with and without job mobility. Multivariate logistic regression was used to analyse whether psychosocial factors could predict job mobility. All regression analyses were stratified by gender. RESULTS: Exposure to a combination of high demands-low control or high imbalance between effort and reward was related to increased odds of changing jobs (OR 1.63; CI 1.03-2.59 and OR 1.46; CI 1.13-1.89 respectively). When analysing men and women separately, men had a higher OR of changing jobs when exposed to either high demands-low control (OR 2.72; CI 1.24-5.98) or high effort-reward imbalance (OR 1.74; CI 1.11-2.72) compared to reference values. The only significant associations for women was slightly decreased odds for turnover in high reward jobs (OR 0.96; CI 0.92-0.99). CONCLUSIONS: The results indicate that workers will seek to improve poor work environment by changing jobs. There were notable gender differences, where men tended to engage in job mobility when exposed to adverse psychosocial factors, while women did not. The lack of measures for mechanisms driving job mobility was a limitation of this study, thus preventing conclusions regarding psychosocial factors as the primary source for job mobility.